Testing and interpreting measures of ovarian reserve: a committee opinion (Fertility and sterility, 2015)
Currently there is no uniformly accepted definition of decreased ovarian reserve (DOR), as the term may refer to three related but distinctly different outcomes: oocyte quality, oocyte quantity, or reproductive potential. Available evidence concerning the performance of ovarian reserve tests is limited by small sample sizes, heterogeneity among study design, analyses and outcomes, and the lack of validated outcome measures.